Respuesta :
Answer:
a_0 = -27
a_n = a_(n-1) * (-1/3)
Step-by-step explanation:
First evaluate given formula at n=0 and specify that as starting value
Then find how to get from n-1 to n by comparing two values. In this case the next value is formed by multiplying by -1/3.
Answer:
[tex]a_n = a_{n-1} \cdot (-\frac{1}{3})[/tex]
Step-by-step explanation:
The explicit formula for the geometric sequence is given by:
[tex]a_n = a_1 \cdot r^{n-1}[/tex]
where,
[tex]a_1[/tex] is the first term
r is the common ratio to the following terms.
As per the statement:
Given the explicit formula for geometric sequence:
[tex]a_n = 9 \cdot (\frac{-1}{3})^{n-1}[/tex]
On comparing with [1] we have;
[tex]a_1 = 9[/tex] and [tex]r = -\frac{1}{3}[/tex]
The recursive formula for geometric sequence is given by:
[tex]a_n = a_{n-1} \cdot r[/tex]
Substitute the given values we have;
[tex]a_n = a_{n-1} \cdot (-\frac{1}{3})[/tex]
Therefore, the recursive formula for the geometric sequence is, [tex]a_n = a_{n-1} \cdot (-\frac{1}{3})[/tex]